Electrochemical Seebeck coefficient of Fe2+/Fe3+ in acetone–methanol mixed solution. (1st June 2022) - Komatsu, Toshiki; Inoue, Dai; Moritomo, Yutaka
Abstract: The electrochemical Seebeck coefficient ( α ) of Fe 2+ /Fe 3+ in acetone–methanol (MeOH) mixed solution was systematically investigated against the acetone molar ratio ( n ) and molar ratio of Fe 3+ to Fe ( n Fe3+ ). At n Fe3+ = 0.75, α monotonously increases with increase in n from 0.3 mV K −1 at n = 0.00 to 3.4 mV K −1 at n = 1.00. At n Fe3+ = 0.50 and 0.25, we found anomalous dip structures in the n − α plot at n ≈ 0.9 and 0.4, respectively. Based on a spectroscopic investigation, we interpreted the observed dip structures in terms of the transition state between the FeCl4 -active and Fe L 6 -active regions.